2012
DOI: 10.1111/ejh.12018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection is associated with deletion of chromosome 8p in multiple myeloma

Abstract: Serological analyses within epidemiological cohort and case-control studies indicate to an association between HBV infection and risk of multiple myeloma (MM). To verify the relationship with an independent approach, we investigated the correlation between HBV positivity and chromosomal aberrations within 680 patients of the National Center for Tumor Diseases Heidelberg for which the serological HBV status (HBsAg and anti-HBc) and FISH data for five gains (1q21, 9q34, 11q23, 15q22, 19q13), five losses (6q21, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…12,13 Deletion of 8p chromosome in patients of MM was observed in 680 patients of the National Center for Tumor Diseases Heidelberg, Germany in approximately 40% HBV-positive patients compared with 20-30% HBV-negative patients. 14 The prevalence of acute and chronic HBV infection in patients with MM was observed in 11.5% and 14.54%, respectively. 15 Thrombocytosis is an atypical feature in MM as these cases are characterized by myelosuppression.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 Deletion of 8p chromosome in patients of MM was observed in 680 patients of the National Center for Tumor Diseases Heidelberg, Germany in approximately 40% HBV-positive patients compared with 20-30% HBV-negative patients. 14 The prevalence of acute and chronic HBV infection in patients with MM was observed in 11.5% and 14.54%, respectively. 15 Thrombocytosis is an atypical feature in MM as these cases are characterized by myelosuppression.…”
Section: Discussionmentioning
confidence: 96%
“…The deletion of 8p chromosome is an important factor in the development of HBV-associated tumors. In hepatocellular carcinoma and MM, the deletion of this chromosome has been observed in ~40% of the patients classified as HBV-positive compared with 20-30% of the patients classified as HBV-negative (24,25). Perhaps due to sample size, Becker et al (25) did not identify a significant difference between 1q21 amplification and the pathogenesis of MM.…”
Section: Hbv Status -------------------------------------------------mentioning
confidence: 94%
“…In hepatocellular carcinoma and MM, the deletion of this chromosome has been observed in ~40% of the patients classified as HBV-positive compared with 20-30% of the patients classified as HBV-negative (24,25). Perhaps due to sample size, Becker et al (25) did not identify a significant difference between 1q21 amplification and the pathogenesis of MM. However, the present study identified a statistically significant gain of 1q21 between the patients classified as HBV-positive compared with the patients classified as HBV-negative.…”
Section: Hbv Status -------------------------------------------------mentioning
confidence: 94%